Landscape expansion-place quality nexus revisited: How fundamental and transitory growth impact in China?. (April 2021) - Zheng, Linzi; Chen, Ke; Tan, Shukui; Yin, Chaohui; He, Qingsong; Wu, Jiayu
Highlights: Inconsistences between demographic, economic and technical (DET) factors and policies affect how compactness affects QoP. Compact growth driven by DET changes are more effective in fostering better QoP. In economically backward cities, policy shocks toward compactness could improve QoP. In relatively developed cities, policy shocks could have attenuated positive impacts of compactness on QoP. Abstract: The conventional wisdom that compact city fosters quality of place (QoP) has been contested in the literature, leaving the nexus between urban expansion and QoP something of a black-box. This paper investigates the magnitude of additional QoP achievements derived from increasing compactness for 362 Chinese cities. We propose that an expansion consists of a fundamental part ( FLE ) in consistency with fundamental factors such as demographic, economic and technical changes and a transitory part ( TLE ) mainly driven by policy shocks, while these two parts would affect QoP heterogeneously. We find that compact FLE has positive effects on QoP, which, however, may be attenuated by TLE . We also discern that positive effects of compactness on QoP are most pronounced in cities located in economically backward areas of the west; and only cities in this region have QoP positively related to compact TLE, indicating that even policy shocks could improve QoP here as long as they are promoting compactness. This research has theoretical contributions and implications for China's urban polies that a move from sweeping directives on urban expansion to connecting with fundamental changes is more effective in fostering QoP.